2016
DOI: 10.1371/journal.pone.0146771
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Treatment May Improve the Survival Rate of Patients with Metastatic Nasopharyngeal Carcinoma with Good Performance Status

Abstract: The aim of the present study was to evaluate the benefit of chemotherapy, combined with palliative radiotherapy (PRT) and other local treatments to the metastatic sites, for patients with metastatic nasopharyngeal carcinoma (NPC) who had a performance status 0–2. We conducted a retrospective review of available data from 197 biopsy-proven NPC patients who developed metastasis after their initial definitive treatment. These patients were grouped into three categories according to the different treatment paths t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 17 publications
3
18
2
Order By: Relevance
“…In addition, poor KPS was identified as an independent risk factor for OS, even if there was no effect on PFS. This finding is consistent with the results of Zheng et al, who found that multimodal treatment could improve the survival of metastatic NPC patients who exhibited a good performance status. Patients with favorable KPS had increased opportunity for posterior‐line therapy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, poor KPS was identified as an independent risk factor for OS, even if there was no effect on PFS. This finding is consistent with the results of Zheng et al, who found that multimodal treatment could improve the survival of metastatic NPC patients who exhibited a good performance status. Patients with favorable KPS had increased opportunity for posterior‐line therapy.…”
Section: Discussionsupporting
confidence: 93%
“…The poor PFS of metachronous metastasis compared to synchronous metastasis may be attributed to greater therapeutic resistance. [23][24][25] We also found that while the combined chemotherapy regimen was an independent prognostic factor for PFS, the optimal chemotherapy regimens were not determined in the current study. Recently, a meta-analysis showed that the triple combination regimen was associated with the best short-term efficacy but failed to improve the patient prognosis among the four commonly used first-line chemotherapy regimens (PF, GP, TP, and triplet combination regimen) for RM-NPC.…”
Section: Discussioncontrasting
confidence: 52%
“…People of smoke, alcohol abuse, and exposure to dangerous chemicals show higher risk of NPC [ 7 ]. Until now, the treatment of NPC still remains as the greatest obstacle, due to the high rate of metastasis [ 8 , 9 ]. Thus, elucidating the mechanisms and screening biomarkers for early diagnosis show great clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…(18) Wei et al showed that among patients with and without multimetastasis, survival was signi cantly better for those receiving chemoradiotherapy than for those receiving chemotherapy alone; moreover, prognosis was better for patients with oligometastasis. (19) To date, however, no studies have reported the e cacy of radiotherapy for improving survival in mNPC patients with single-organ vs. multiorgan metastases. In the clinic, the attending doctor tends to choose patients with single-organ metastasis for primary local radiotherapy, because these patients have better treatment tolerance and better prognosis, and are more likely to have a longer survival time.…”
Section: Discussionmentioning
confidence: 99%